Multicellular tumor spheroid formation in duplex microcapsules for analysis of chemosensitivity - Sakai, Shinji (Cancer Sci, 2012)
Multicellular tumor spheroids (MTS) are gaining increased recognition as valuable tools and key elements in anticancer drug discovery and tumor therapy test programs. However, the lack of reproducible and uniform MTS sizes is a major problem for pharmaceutical assays. Here, we show the usefulness of duplex microcapsules with a Ca‐alginate gel membrane as a platform for producing MTS with a highly homogeneous size distribution. HeLa cells were enclosed with 86.9% viability within the microcapsules. The enclosed cells grew and formed MTS with the same size as the cavity of the microcapsules by arresting their growth with the microcapsule membrane. The cells in the resultant MTS had a higher proportion in G(0)/G(1) phase (71.2%) than 2‐D cultured cells in the stationary phase (64.3%) or those in MTS formed on a non‐adherent surface (65.3%) (P < 0.01). Furthermore, the cells in MTS formed within microcapsules showed higher tolerance to mitomycin C (1–1000 nM) and gemcitabine (4.5–4500 nM) than 2‐D cultured cells (P < 0.01). In addition, the expression of MDR1, MCT1, HIF‐1α, and GRP78 mRNA was 2.9‐, 3.2‐, 3.8‐, and 5.5‐fold higher, respectively, than those in 2‐D cultured cells (P < 0.04). Cryopreserved encapsulated cells in the microcapsules showed 80.5% viability and formed MTS with a comparable tolerance of 100 and 1000 nM mitomycin C to those that were not cryopreserved (P > 0.09). These findings suggest the duplex microcapsule may be a promising tool for producing MTS for pharmaceutical applications. (Cancer Sci 2012; 103: 549–554)